Anticorpos contra Chlamydia trachomatis e síndrome metabólica - Sehnem, Luciele (Pontifícia Universidade Católica do Rio Grande do Sul, 2013)
Made available in DSpace on 2013-08-07T19:04:49Z (GMT). No. of bitstreams: 1 000422377-Texto+Completo-0.pdf: 884424 bytes, checksum: 00e9c69f02bdc012c466f39cf67939e7 (MD5) Previous issue date: 2010 === The metabolic syndrome (MS) comprises a cluster of risk factors for atherosclerotic disease. Pathogens such as Chlamydia pneumoniae and Helycobacter pylori may be involved on triggering and perpetuation of atherogenesis, but their relationship with MS is rather unknown. Exposition to Chlamydia trachomatis (CT) in patients with MS has been unexplored in the literature up to date. Objective: to evaluate the association, if any, of IgA and IgG anti-CT antibodies and occurrence of MS. Methods: in this cross-sectional study, patients with MS with and without previous cardiovascular disease and age and age and sex-matched controls were evaluated. MS diagnosis was based on NCEP criteria. IgA and IgG anti-CT antibodies were detected by immunoenzymatic assay; titers above 1. 1 units were considered as positive. The chi-squared test was utilized for comparison of categoric variables, and the t test for continuous variables. To estimate the association of anti-CT antibodies and MS, odds ratios were calculated. Logistic regression was utilized for adjustment of age and sex. Results. The total survey included 238 individuals: 101 patients (42. 5%) with MS without cardiac events; 47 (19. 7%) with MS and previous cardiac events; and 90 (37. 8%) healthy controls. Females predominated in the 3 groups of patients. The global mean age was 59. 7 years. The prevalence of a positive test for IgA anti-CT was higher in patients with MS (17%) than in controls (6%) (P=0. 015). Elevated levels of IgA anti-CT associated significantly with occurrence of MS in comparison to healthy controls after adjustment for sex and age (OR=3. 4; CI95% 1. 2-9,4; P=0. 015). In the subgroup analysis, elevated levels of IgA anti-CT were more prevalent in non-complicated MS than in controls (P=0. 013). After adjustment for age and sex, the association of IgA anti-CT with non-complicated MS remained defined (OR=3. 6; CI95% 1. 32-10,2; P=0. 015). Conclusions: IgA anti-CT antibodies, possibly of acute phase, were more prevalent in MS than in healthy controls. A positive test for IgA anti-CT associated particularly to noncomplicated MS. The role of such IgA response in patients with MS should be detailed in forecoming studies. === A síndrome metabólica (SM) compreende um conjunto de fatores de risco para doença aterosclerótica. Patógenos como Chlamydia pneumoniae e Helicobacter pylori podem estar envolvidos no deflagramento e perpetuação da aterogênese, mas sua relação com a SM é desconhecida. A exposição à Chlamydia trachomatis (CT) em pacientes com SM não foi explorada na literatura até o momento. Objetivo: Avaliar a associação, se existente, entre anticorpos IgA e IgG anti-CT e ocorrência de SM. Métodos: Neste estudo transversal, foram avaliados pacientes com SM com e sem eventos cardíacos prévios e controles sadios pareados por sexo e idade. O diagnóstico de SM se fundamentou nos critérios do NCEP. Anticorpos IgA e IgG anti-CT foram detectados por ensaio imunoenzimático; títulos acima de 1,1 unidades foram considerados positivos para ambos os isotipos. O teste do qui-quadrado foi utilizado para comparação das variáveis categóricas, e o teste t para comparação de variáveis contínuas. Para estimar a associação entre anticorpos anti-CT e SM, odds ratios (OR) foram calculados. Regressão logística foi utilizada para o ajuste das variáveis sexo e idade. Resultados: O número total da amostra foi de 238 indivíduos: 101 pacientes (42,5%) com SM sem eventos cardíacos; 47 (19,7%) com SM e eventos cardíacos prévios; e 90 (37,8%) controles sadios. O sexo feminino predominou nos 3 grupos. A média global de idade foi 59,7 anos. A prevalência de teste positivo para IgA anti-CT foi maior em pacientes com SM (17%) do que em controles (6%) (P=0,015). Níveis elevados de IgA anti-CT se associaram significativamente com ocorrência de SM na comparação com controles sadios após ajuste para sexo e idade (OR=3,4; IC95% 1,2-9,4; P=0,015). Na análise de subgrupos, níveis elevados de IgA anti-CT foram mais prevalentes na SM não-complicada do que nos controles (P=0,013). Após ajuste para sexo a idade, a associação entre IgA anti-CT e SM nãocomplicada se manteve definida (OR=3,6; IC95% 1,32-10,2; P=0,015). Conclusões: Anticorpos IgA anti-CT, possivelmente de fase aguda, foram mais prevalentes na SM do que em controles sadios. Um teste positivo para IgA anti-CT se associou particularmente à ocorrência de SM não-complicada. O papel da resposta IgA anti- CT em pacientes com SM deve ser detalhado em estudos futuros.